Housing demand: mobile, modular, or conventional? - Davidson, Harold A. (New York : Van Nostrand Reinhold Company, Inc., 1973)
The purpose of this book is to provide a perspective of the mobile home market useful to the home buyer; housing manufacturer; developer; zoning administrator; lender; investor; student of housing, urban development, and urban planning; and anyone interested in the total housing market.
Preface -- Acknowledgments -- List of tables -- List of graphs -- List of illustrations -- 1. Introduction -- 2. Evolution of the mobile home industry -- 3. Analysis of current and future total housing market -- 4. Impact of modular and low-cost housing on the housing market and its influence on mobile home demand -- 5. Determinants of the demand for mobile homes -- 6. Projection of the demand for mobile homes through 1980 with implications for the financial structure of the industry -- 7. Summary and conclusion.
Includes bibliographical references and index.
Keywords: AUTOMOBILE TRAILERS